Granulomatous Mastitis: Unusual Presentation and Management, Experience at Birdem General Hospital (Medicine Today, 2018)
Tuberculosis of breast is an unusual presentation of extrapulmonary tuberculosis. It occurs mostly in women who are of reproductive age group, multiparous and lactating. Common presentation is tumor like but patients of our study group mostly presented with abscess and mastitis. This study was carried out at BIRDEM GENERAL HOSPITAL, ShegunBagicha, Dhaka. Retrospective data of 9 patients with breast tuberculosis was analyzed. Information about demographic details, clinical presentation, cytology, histopathology, comorbidity and management was taken into account. Out of 1202 patients who presented with breast problem during the study period only 9 (0.75%) suffered from tuberculosis of breast. Their age ranged from 20 to 55 years. All patients except 2 presented with abscess formation, 1 with lump and 1 with multiple sinuses. All patients were subjected to histopathology. Their pathological examination showed chronic granulomatous inflammation with caseous necrosis and langerhans giant cells suggestive of tuberculosis. All 9 patients were treated with Anti TB drug therapy after adequate surgical intervention when required. The rare entity tubercular mastitis is a disease of relatively younger age group. Though the usual presentation is tumor like, the patients of the study group mainly presented with abscess formation. Diabetes might be a contributing factor for the unusual presentation among the patients of my study group.Medicine Today 2018 Vol.30(2): 78-80